2016
DOI: 10.1155/2016/3468246
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Numerical Simulations of Heat Distribution for LED Heat Sink

Abstract: Light-emitting diode (LED) has higher efficiency and longer lifetime when compared with the conventional lighting. However, the efficiency and lifetime will be degraded greatly when it is operated at a high temperature. Now, both previous simulation and experimental results have already indicated that the heat transfer in vertical direction of the LED lamp by conduction is the most critical component. In this paper, a simplified numerical simulation model is built to estimate the heat distribution of the LED h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The temperature of the solar cell was reduced to 10°C and its electrical power capability was increased to 7.55%. Modeling and simulations of heat sinks conducted by Zhu and Sun [24] showed that a simple heat sink can affect the longevity of semiconductor material. Research by Luo et al [25] used an experimental method to demonstrate several heat sinks with flared fin configurations and obtained an overall reduction in thermal resistance of up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the solar cell was reduced to 10°C and its electrical power capability was increased to 7.55%. Modeling and simulations of heat sinks conducted by Zhu and Sun [24] showed that a simple heat sink can affect the longevity of semiconductor material. Research by Luo et al [25] used an experimental method to demonstrate several heat sinks with flared fin configurations and obtained an overall reduction in thermal resistance of up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is a frequent procedure in the industry to perform computer simulations for complex systems instead of building numerous physical models of a device, which leads to savings in time and money [3]. For example, the subject of optimizing the size and shape of heat sinks for various lighting devices is now widely researched, especially in the field of numerical modeling, e.g., [4]. Frequently discussed in the literature is the cooling of light-emitting diode (LED) lamps with the use of natural and forced convection, e.g., [5][6][7].…”
Section: Introductionmentioning
confidence: 99%